Issues in the Language Policy of the European Union. Motivation as a Key Factor in Promoting Language Learning - Komorowska, Hanna (Glottodidactica, 2007)
As motivation has been identified by the EU High Level Group on Multilingualism as the key factor in promoting language education, the author, herself member of HLGM, discusses a variety of approaches to motivation and presents guidelines for the promotional activity at national, regional and school levels, concentrating on its aims and procedures, identifying age groups and motives to be targeted, as well as arguments and strategies to be used in the process of eliciting and sustaining learners' motivation to study foreign languages.